The Pemetaan Daerah Rawan Tanah Longsor Menggunakan Sistem Informasi Geografis Di Kecamatan Patuk, Kabupaten Gunungkidul - ridwan, ardian (ReTII, 2020)
Landslide disaster is a disaster that often occurs in the Patuk Subdistrict area during the rainy season which flushed the Gunung Kidul Regency, Yogyakarta Special Region. The role of the geographic information system to see the level of landslide vulnerability in Patuk District is very important to minimize the occurrence of disasters in the area. The purpose of this study is to conduct a landslide hazard mitigation modeling using a Geographical Information System. Disaster mitigation modeling is carried out by utilizing secondary data in the form of rainfall data, geological data, land use data, slope data, soil type data, and landform data which are then carried out overlay analysis or a method of combining several data to determine the level of landslide hazard. The results showed that Patuk Subdistrict had a landslide hazard level which was dominated by a moderate landslide hazard category of 6645 hectares, a high landslide hazard category of 351, 64 hectares, and a low landslide hazard category of 61.91 hectares. Keywords: geographic information system, landslide hazard, disaster mitigation